Factors Related to Occupational Diseases in Smelter Employees PT. Virtue Dragon Nickel Industry Site Morosi - Rahayu, Tri; Sunarsih, Sunarsih; Azizi Jayadipraja, Erwin (Magister Kesehatan Universitas Mandala Waluya, 2023)
Introduction: In Indonesia, the number of cases of disease events continues to increase every year, there is no increase in PT. Virtue Dragon Nickel Industry that is one of the largest industries in Southeast Sulawesi Province where the number of cases of occupational diseases also continues to increase. Method: Research using a cross-sectional research design. The research location is at PT. Virtue Dragon Nickel Industry Mega industrial area of Konawe district. The sample in this study was 100 employees who worked especially in the smelter unit. To find out the relationship between the dependent variable and the independent variable, it was carried out using the Chi-Square test with a significant level (α= 0.05). Result: This study shows that There is a significant relationship between working hours and the incidence of occupational diseases in employees of PT. Virtue Dragon Nickel Industry p-value = 0.000. There is a relationship between noise and the incidence of occupational diseases in employees of PT. Virtue Dragon Nickel Industry p-value=0.000. Conclusion: Working hours and noice have a relationship with the incidence of occupational diseases at PT. The Dragon of Virtue Nickel Industry.